Application of the Game Based Learning Model to Improve Classroom Students' Drama Text Learning Outcomes VIII-A Smp Negeri 22 Surabaya - Christaningtyas, Windi; Yuniseffendri; Widyarini, Tri Wahanani (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This research is classroom action research which aims to determine the application of Game Based Learning to improve the learning outcomes of Drama Texts for 32 students in class VIII-A at SMP Negeri 22 Surabaya. This is because students' understanding of the material regarding the structure and elements of drama texts is still lacking, so the learning outcomes are still lacking and not yet within the predetermined criteria. The research began with an interview method with subject teachers to determine students' initial understanding, the method used to determine students' initial conceptual understanding. The research was carried out in two stages, namely cycle I and cycle II. Each cycle consists of a process of planning, action, observation and reflection. Test results using the Game Based Learning learning model have increased starting from the pre-test which obtained an average score of 46.8. In cycle I, the average test results obtained by students were 68.75. In cycle II, an average value of 87.5 was obtained